Effects of Al2O3 content on densification, microstructure, mechanical properties and oxidation resistance of TaC-Al2O3 composites. (January 2019) - Lu, Zhuang; Liu, Limeng; Hou, Zhaoping; Zhang, Biao; Geng, Guihong; Wang, Yujin; Ye, Feng
Abstract: TaC-Al2 O3 composites were prepared by hot pressing. Influence of Al2 O3 content ranging from 10 to 40 vol. % on densification, phase composition, microstructure, mechanical properties and oxidation behavior of the TaC-Al2 O3 composites was investigated. With 30 and 40 vol. % Al2 O3 addition a closed porosity was achieved. The Al2 O3 particles were uniformly distributed among TaC grains retarding grain growth and resulting in refined microstructures with grains below 2 μm in size. The most densified composite with 40 vol. % Al2 O3 addition exhibited good mechanical properties with a Vickers' hardness of 17.8 GPa, a flexural strength of 485 MPa and a fracture toughness of 5.4 MPa·m 1/2 . After holding at 700°C for 3 h in air, the dense 30 and 40 vol. % Al2 O3 compositions showed hardly noticeable and mainly surface oxidation, whereas less densified TaC-Al2 O3 composites with 10 and 20 vol. % Al2 O3 content and with open porosity were disintegrated to powders. Highlights: TaC-Al2 O3 composites with 10-40 vol% Al2 O3 were prepared by hot pressing. Satisfying densification could be reached at 30 vol% Al2 O3 addition and above. The dense TaC ceramics with 30-40 vol% Al2 O3 had good mechanical properties. Oxidation resistance was significantly improved by adding 30-40 vol% Al2 O3 .